2016
DOI: 10.1016/j.ajpath.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Spleen Tyrosine Kinase Signaling Promotes Myeloid Cell Recruitment and Kidney Damage after Renal Ischemia/Reperfusion Injury

Abstract: Ischemia/reperfusion (I/R) injury is an important cause of acute and chronic renal failure. Neutrophils and macrophages, by integrin-based recruitment, play a key role in renal I/R injury. Integrin-based activation of spleen tyrosine kinase (Syk) contributes to myeloid cell adhesion to activated endothelial cells in vitro; however, whether Syk is required for myeloid cell recruitment and tubular damage in I/R injury is unknown. Therefore, we investigated the function of Syk in mouse I/R injury using two differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…GS-642362 treatment dramatically reduced neutrophil infiltration into the kidney following IRI. This may reflect a reduction in the release of DAMPs as a result of reduced tubular cell damage, thereby reducing the recruitment and activation of neutrophils, which contribute to a "second wave" of tubular cell death in models of renal IRI [30][31][32]. Extracellular CypB can induce the chemotaxis of inflammatory cells into damaged tissues [33], although no studies of CypB−/− mice in IRI models have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GS-642362 treatment dramatically reduced neutrophil infiltration into the kidney following IRI. This may reflect a reduction in the release of DAMPs as a result of reduced tubular cell damage, thereby reducing the recruitment and activation of neutrophils, which contribute to a "second wave" of tubular cell death in models of renal IRI [30][31][32]. Extracellular CypB can induce the chemotaxis of inflammatory cells into damaged tissues [33], although no studies of CypB−/− mice in IRI models have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral IRI surgery was performed in groups of 10 male C57BL6/J mice using ketamine and xylazine anesthesia as previously described [31]. A heating blanket connected to a rectal thermometer was used to keep body temperature at 37 • C. Following a midline abdominal incision, non-traumatic vascular clamps were used to clamp both renal pedicles for 17 min after which clamps were removed kidney reperfusion checked visually.…”
Section: Renal Ischaemia/reperfusion Injury (Iri)mentioning
confidence: 99%
“…Rats underwent bilateral IRI, as previously described. 14,15 Male rats were anesthetized with ketamine and xylazine. A heating blanket connected to a rectal thermometer was used to maintain body temperature at 37 C. Following a midline abdominal incision, both renal pedicles were clamped using non-traumatic vascular clamps for 25 minutes, during which the abdomen was temporarily sutured.…”
Section: Bilateral Irimentioning
confidence: 99%
“…Neutrophil infiltration is a prominent response to renal IRI and plays a significant role in the induction of tubular necrosis [23][24][25]. In this study, WT mice exhibited a marked neutrophil infiltrate in the area of tubular damage (Figure 3A,B).…”
Section: Cypa Deletion Protects Against Leukocyte Infiltration In Renal Irimentioning
confidence: 50%